The Role of Current Ratio, Operating Cash Flow and Inflation Rate in Predicting Financial Distress: Indonesia Stock Exchange - Setyawati, Irma; Amelia, Rizki (JDM (Jurnal Dinamika Manajemen), 2018)
We believe company financial statements can be used as a tool to analyze and also as an indicator to know the financial performance. The financial statements contain information for various financial ratios, which are an important tool for assessing the company’s financial performance in the future. The purpose of this research is to know the role of the current ratio, operating cash flow, and the inflation rate in predicting financial distress of consumer goods industry sector listed in the Indonesia Stock Exchange period 2011–2015. Financial distress prediction models need to be developed to assist managers in overseeing company performance and help identify important trends. To analyze the current ratio, operating cash flow, and the inflation rate has a probability of occurring financial distress for the company, used logistic regression. From this study resulted in the finding that the probability of a company exposed by financial distress is caused by operating cash flow, while the current ratio and the inflation rate have a smaller probability of the company of consumer goods to be exposed by financial distress.